Directing structural change: from tools to policy - Tilman Altenburg; Maria Kleinz; Wilfried Lütkenhorst (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Structural change towards diversification and competitiveness is important to make our economies productive, wealthy and sustainable. In market economies, structural change is essentially driven by private entrepreneurs who challenge incumbents with new business ideas and take risks to implement them. While public policy cannot fully anticipate the outcomes of such market-driven search processes, it does have important roles in directing structural change: it can facilitate stakeholder processes meant to overcome coordination and information failure and thereby smooth the transformation; it can make pre-competitive investments in infrastructure and skills for the future; and it can help align structural change with broader societal objectives, such as environmental sustainability or job creation. To fulfil these roles, policymakers need to have an idea about future competitive patterns of specialisation. The challenge is to anticipate trends and facilitate action towards promising futures in ways that are as evidence-based as possible and effectively synchronised with market forces. Our paper makes three essential contributions to addressing this challenge: (1) We identify five influential methodologies for anticipating future competitive advantages, analyse their strengths and weaknesses, and suggest ways to consolidate their most valu¬able features in one synthetic approach. (2) In doing so, we emphasise the importance of disruptive change, stemming in particular from decarbonisation as well as the digitali¬sation of economic processes and products. Such game changers are likely to affect virtually all economic sectors, thereby reducing the predictive power of methodologies that essentially extrapolate from the past. (3) We highlight the need to contextualise the various analytical tools, and caution against using them as technocratic blueprints. To be of practical use, evidence-based assessments of future competitive advantages need to be embedded into a political economy framework that takes account of both societal objectives (normative level) and implementation capabilities (institutional level).
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung; Handel und Investitionen